2010
DOI: 10.1590/s1516-35982010001200023
|View full text |Cite
|
Sign up to set email alerts
|

Consumo, digestibilidade aparente e dias de coleta total na estimativa da digestibilidade em caprinos alimentados com dietas contendo cana-deaçúcar tratada com óxido de cálcio

Abstract: RESUMO -O trabalho foi realizado para avaliar o consumo, a digestibilidade aparente dos nutrientes e o efeito do tempo (dias) de coleta total (dois e quatro dias) na estimativa da digestibilidade aparente em caprinos alimentados com dietas contendo cana-de-açúcar tratada com óxido de cálcio (CaO). Foram utilizados oito caprinos da raça Saanen, machos castrados, com peso corporal médio de 22,6 kg e 4 meses de idade, distribuídos em dois quadrados latinos 4 × 4, com quatro períodos experimentais de 14 dias. As d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…In the literature, studies have reported divergent results for apparent digestibility on hydrolyzed sugarcane diets if compared with fresh sugarcane diets (Dias, 2009;Carvalho et al, 2010;Pina et al, 2010). A number of studies on in vitro methodology found an increased sugarcane digestibility by adding lime (Oliveira et al, 2007;Dias, 2009;Mota et al, 2010), though their results are contested due to possible bias associated to in vitro methodology, causing divergent results from those obtained by the in vivo method (Detmann et al, 2005;Carvalho et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the literature, studies have reported divergent results for apparent digestibility on hydrolyzed sugarcane diets if compared with fresh sugarcane diets (Dias, 2009;Carvalho et al, 2010;Pina et al, 2010). A number of studies on in vitro methodology found an increased sugarcane digestibility by adding lime (Oliveira et al, 2007;Dias, 2009;Mota et al, 2010), though their results are contested due to possible bias associated to in vitro methodology, causing divergent results from those obtained by the in vivo method (Detmann et al, 2005;Carvalho et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…A number of studies on in vitro methodology found an increased sugarcane digestibility by adding lime (Oliveira et al, 2007;Dias, 2009;Mota et al, 2010), though their results are contested due to possible bias associated to in vitro methodology, causing divergent results from those obtained by the in vivo method (Detmann et al, 2005;Carvalho et al, 2010). Different results may certainly be expected depending whether in vitro or in vivo methodology is preferred, as most studies in vitro evaluated the forage, while most studies in vivo evaluated the diets.…”
Section: Resultsmentioning
confidence: 99%
“…The neutral detergent fiber (NDF) contents were estimated as recommended by Mertens et al (2002). The corrections for the levels of ash and protein contained in NDF and ADF were conducted as recommended by Mertens et al (2002) and Licitra et al (1996) cited by Carvalho et al (2010). The total carbohydrates were calculated according to methodology described by Sniffen et al (1992).…”
Section: Measurementsmentioning
confidence: 99%